2007
DOI: 10.1016/j.econlet.2007.01.018
|View full text |Cite
|
Sign up to set email alerts
|

Weak instruments and weak identification, in estimating the effects of education, on democracy

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
55
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(61 citation statements)
references
References 8 publications
(16 reference statements)
5
55
0
1
Order By: Relevance
“…This is a major reason why the BB estimator was developed. Crucially, lagged income is significant 10 times out of 12 when using BB, the state of the art dynamic panel estimator, confirming with a longer panel results found in Bobba and Coviello (2007). Moreover, BB estimation passes all of the specification tests when using the full sample, even though a limited number of instruments was chosen in order to avoid instruments proliferation problems.…”
Section: Democracy and Incomesupporting
confidence: 73%
See 1 more Smart Citation
“…This is a major reason why the BB estimator was developed. Crucially, lagged income is significant 10 times out of 12 when using BB, the state of the art dynamic panel estimator, confirming with a longer panel results found in Bobba and Coviello (2007). Moreover, BB estimation passes all of the specification tests when using the full sample, even though a limited number of instruments was chosen in order to avoid instruments proliferation problems.…”
Section: Democracy and Incomesupporting
confidence: 73%
“…They found that, after controlling for country fixed-effects, GDP per capita was no longer a significant determinant of democracy. 3 In other recent studies, Bobba and Coviello (2007) as well as Castello-Climent (2008) re-examined the evidence. The former isolated a significant effect of GDP per capita using a system-GMM estimator, while the latter found a significant effect of education attained by the majority of population, even after controlling for fixed-effects.…”
Section: Introductionmentioning
confidence: 91%
“…In addition, for several bloggers, these variables have high persistence, thus causing an additional weak-instruments concern. 9 Nevertheless, by relying on various specification of system generalized method of moments (GMM) (Arellano and Bover, 1995;Blundell and Bond, 1998;Roodman, 2009a), and by paying attention to weak identification (Bobba and Coviello, 2007) and instruments proliferation (Roodman, 2009b), we obtain results in line with theoretical predictions.…”
Section: The Econometric Modelsupporting
confidence: 61%
“…Another di¤erence is that the coe¢ cient of human capital decreases and becomes insigni…cant in several speci…cations. Recall that the literature on education and democracy is inconclusive: while Acemoglu et al (2008) found that education has no explanatory power for democracy, Bobba and Coviello (2007) or Castello-Climent (2008) found a positive and signi…cant e¤ect. Our results suggest that the e¤ect might be there but does not prove to be highly robust to speci…cation choices.…”
Section: Panel Analysis With Sys-gmmmentioning
confidence: 99%
“…In columns 3 to 8, we show that our results are robust to the inclusion of additional standard control variables such as absolute geographic variables (latitude, a landlocked dummy variable, area (log) is sq.kms, percentage of malaria area in 1994, percentage of land area in geographical tropics), regional dummies, ethnic fractionalisation and legal origin dummies, and other potential determinants of institutional quality such as GDP per capita, trade (imports + exports as percentage of GDP) 14 and foreign aid (ODA as a percentage of GNI). 15 The inclusion of these control variables does not a¤ect the signi…cance of the emigration coe¢ cient. The coe¢ cient is globally stable, except when we consider the polity2 indicator and control for geographical explanatory variables and regional dummies (colums 4 and 5).…”
Section: Cross-sectional Analysismentioning
confidence: 99%